Thrombocytopenia as a Preoperative Risk Assessment Tool in Patients With Rheumatic Heart Disease Undergoing Valve Replacement Surgery - Wei, Xue‐biao; Jiang, Lei; Liu, Yuan‐hui; Feng, Du; He, Peng‐cheng; Chen, Ji‐yan; Tan, Ning; Yu, Dan‐qing (Journal of the American Heart Association, 2017)
Background Postoperative thrombocytopenia has been reported to be correlated with adverse events, but the prognostic value of baseline thrombocytopenia is unclear. This study was undertaken to evaluate the relationship between preoperative thrombocytopenia and adverse outcomes in patients with rheumatic heart disease who underwent valve replacement surgery. Methods and Results A total of 1789 patients with rheumatic heart disease undergoing valve replacement surgery were consecutively enrolled and postoperatively followed up for 1 year. Patients were stratified on the basis of presence (n=495) or absence (n=1294) of thrombocytopenia (platelet count, <150×109/L), according to hospital admission platelet counts. During the hospitalization period, 69 patients (3.9%) died. The in‐hospital all‐cause mortality rate was significantly higher in the thrombocytopenic group (6.9% versus 2.7%; P<0.001). Multivariate analyses revealed that thrombocytopenia was independently associated with in‐hospital all‐cause mortality (odds ratio, 2.21; 95% confidence interval, 1.29–3.80; P=0.004). Platelet counts could predict in‐hospital all‐cause mortality for patients both with and without previous atrial fibrillation (areas under the curve, 0.708 [P<0.001] and 0.610 [P=0.025], respectively). One‐year survival was significantly lower in patients with thrombocytopenia compared with controls (91.3% versus 96.1%; log‐rank=14.65; P<0.001). In addition, thrombocytopenia was an independent predictor for postoperative 1‐year all‐cause mortality in multivariate Cox regression analysis. Conclusions Platelet counts, as simple and inexpensive indexes, were reliable to be used as a preoperative risk assessment tool for patients with rheumatic heart disease undergoing valve replacement surgery.